Dynamic p53 protein expression and phosphorylation in the kidneys of rats that experienced intrauterine growth restriction. (27th February 2015) - He, Xiaori; Xie, Zongde; Dong, Qingyi; Chen, Pingyang; Li, Wen; Wang, Tao
Abstract: Aim : This study investigated the mechanisms involved in intrauterine growth restriction (IUGR). Methods : The IUGR model was established by feeding pregnant SD rats a low-protein diet. Protein expression and phosphorylation were detected using Western blot and/or immunohistochemistry. Cell apoptosis was detected by TUNEL staining. The MDM2 mRNA expression was measured by real-time PCR. Results : Pups from the IUGR group had significantly lower body (7th day, 2 months) and kidney weights (1st day, 7th day, 2 months) compared to pups from the control group ( p < 0.01). The glomeruli number in IUGR pups was significantly less than that in the control pups at 2 and 3 months after birth ( p < 0.01). p53 protein level and p53 phosphorylation at Ser 15 were time-dependently decreased in the kidney at 1st day, 7th day, 21st day, 2 months and 3 months, but their levels in the kidney of the IUGR pups was significantly higher than that in control pups at each time point ( p < 0.05, p < 0.01, or p < 0.001). Significantly more positive p21 staining was observed in IUGR pups than in control pups at each time point. Real-time PCR of MDM2 mRNA expression showed no significant difference between IUGR and control pups ( p > 0.05). Significant apoptosis was observed in the kidneys of IUGR pups compared to control pups. Conclusion : Malnutrition-induced IUGR may be associated with the activation of p53–p21 signaling in the kidney.